The Impact of Personality Types on Students’ Writing Ability - Zaswita, Hermi; Ihsan, Rodiyal (JPI (Jurnal Pendidikan Indonesia), 2020)
Personality is considered one of the internal factors that have an impact on students’ ability in language learning. The present study investigated the impact of personality types on their ability in writing English. There are two types of personalities studied: Extrovert and Introvert. The research is quasi-experiment. Students at grade XI Vocational School 1 Sungai Penuh engage in the study, whereas only two classes selected as samples (experimental class and control class). Students were given a personality questionnaire to recognize their personality types. Then, the writing test carries out in each class in order to know the student's ability in writing. The data are analyzed by using t-test. The finding of hypotheses testing proves that the p-score is 0,00. Thus, the p-score is lower than 0,05 (0,00<0,05) which means H0 is rejected and H1 is accepted. Hence, there is a significant impact on students’ personalities to their writing ability. Students with introvert personalities have better writing scores than students with extrovert personality.